Effects of micronized okara dietary fiber on cecal microbiota, serum cholesterol and lipid levels in BALB/c mice. (24th July 2013) - Li, Ti; Zhong, Jun-Zhen; Wan, Jie; Liu, Cheng-Mei; Le, Bi-Yun; Liu, Wei; Fu, Gui-Ming
Abstract: Micronized by a dry grinding method (D-ODF) or a wet granulating method (W-ODF), okara dietary fiber (ODF), was fed to BALB/c mice for 28 d. The water holding capacity of D-ODF and W-ODF was significantly enhanced after micronization. W-ODF had a larger swell capacity and a higher content of soluble dietary fiber than crude ODF and D-ODF. After feeding for 28 d, the populations of Escherichia coli and Lactobacilli in the cecum were significantly lower and higher in the W-ODF group than other groups, respectively, while the population of Bifidobacterium increased in all groups. The effect of each diet on the population of E. coli. Lactobacilli and Bifidobacterium was all maintained for a short period of time except that the effectiveness of W-ODF diet on the Bifidobacterium population lasted slightly longer than other diets. At the end of the feeding period, serum total cholesterol (TC) and triglyceride in D-ODF and W-ODF diets were significantly lower and HDL-C/TC ratio was significantly higher than those in crude ODF.